Peran PNI dalam Membentuk Konsep Nasionalisme 1927-1936 - Nukman - (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
The role of PNI (Partai Nasional Indonesia) movement organization which was dominated by intellectuals was very influential in the process of forming nationalism. The changes that are felt, especially in the field of education, are influenced by programs that are systematically structured so that the legal bargaining process can be carried out in court without the need for violence. This paper will explain the role of PNI movement organization in building nationalism steps to strengthen and influence in society. The method used in this research is library research. The result of this research is that the PNI movement organization made an effort to build nationalism in various ways, namely by establishing courses, establishibg schools, banks and also strengthening public opinion on PNI’s goals by holding public meetings and publishing media such as Banteng Priangan and Persatoen Indonesia newspapers.